A molecular imprinting electrochemical sensor and a method for detecting folic acid content thereof

Synthesis of molybdenum disulfide-carbon dot composite material through solvent thermal method to modify the glass carbon electrode and prepare molecular imprint electrochemical sensors, which solves the problems of long detection cycle, expensive equipment and low sensitivity of the existing folic acid detection method, and realizes neutral conditions Fast and accurate detection under the hood, high sensitivity and anti-interference.

CN112067674BActive Publication Date: 2024-12-20ANHUI XINHONG PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202011062427.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-09-30
Publication Date
2024-12-20
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

The existing folic acid detection methods have problems such as long detection cycle, expensive equipment, poor reproducibility, toxic organic matter, low sensitivity, and the need for pretreatment to remove matrix interference.

Method used

The solvothermal method is used to synthesize molybdenum disulfide-carbon dot composite material, modify the glass carbon electrode, and prepare molecular imprinting electrochemical sensors through electrochemical polymerization. Combined with molecular imprinting technology, specific identification and detection of folic acid is achieved.

Benefits of technology

It realizes rapid and accurate detection of folic acid under neutral conditions, and has the effect of simple operation, low cost, high sensitivity and strong anti-interference. The detection limit is 0.09μmol/L, which can be between 60μmol/L-5000μmol/L Linear response within the concentration range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112067674B_ABST
    Figure CN112067674B_ABST
Patent Text Reader

Abstract

The present invention discloses a molecular imprinting electrochemical sensor and a method for detecting folic acid content thereof, and belongs to the field of electrochemical detection technology. The present invention adopts a solvothermal method to synthesize a molybdenum disulfide-carbon dot composite material, modifies a glassy carbon electrode with a molybdenum disulfide-carbon dot composite material solution, and then uses o-phenylenediamine as a functional monomer to prepare a molecular imprinting electrochemical sensor having a specific recognition response to the template molecule folic acid on the surface of the glassy carbon electrode modified with molybdenum disulfide-carbon dot by electrochemical polymerization. The molecular imprinting electrochemical sensor prepared by the present invention has a specific response to folic acid, a detection limit of 0.09 μmol / L, good sensitivity, and strong anti-interference.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molecular imprinting electrochemical sensor and a method for detecting folic acid content thereof, belonging to the technical field of electrochemical detection. Background Art

[0002] Folic acid, also known as pteroylglutamic acid, is a water-soluble vitamin B that is widely found in some fresh fruits, green vegetables, animal livers and beans. Since the human body cannot synthesize folic acid on its own, it can only absorb exogenous folic acid through the intestines, which often leads to the occurrence of folic acid deficiency. Folic acid deficiency can lead to physiological dysfunction and certain diseases, such as neural tube defects in newborns, osteoporosis and mental degenerative diseases, so the intake and supplementation of folic acid has gradually become a health issue that the whole world is concerned about. With the continuous deepening of folic acid research, some health problems caused by excessive intake of folic acid have gradually increased, such as zinc deficiency, nausea, anorexia and a series of gastrointestinal symptoms. Therefore, the reasonable intake of folic acid is particularly important. Rapid and accurate detection of folic acid content is an important technical means to guide folic acid intake and ensure its safety and effectiveness. It is also an effective indicator for diagnosing various diseases and is of great significance for clinical diagnosis.

[0003] At present, many methods for detecting folic acid have been developed and are becoming more and more perfect. Among the methods that have been reported, the microbial method is generally recognized as the preferred option because of its wide measurement range and low cost, but it requires a longer detection cycle. High performance liquid chromatography and liquid chromatography tandem mass spectrometry have good selectivity, but there are still problems such as expensive equipment and long time consumption in the analysis process. Capillary electrophoresis has the advantages of small sample amount and high separation efficiency, but there are problems such as poor reproducibility and toxic organic matter. Colorimetry and enzyme-linked immunosorbent assay are fast in detection, but low in sensitivity, and pretreatment is required to remove interference in the matrix. Summary of the invention

[0004] [Technical issues]

[0005] Current methods for detecting folic acid include microbiological method, high performance liquid chromatography and liquid chromatography-tandem mass spectrometry, capillary electrophoresis, colorimetry and enzyme-linked immunosorbent assay, etc. However, these methods have problems such as long detection cycle, expensive equipment, poor reproducibility, toxic organic matter, low sensitivity, and the need for pretreatment to remove interference in the matrix.

[0006] [Technical solution]

[0007] In view of the above problems, in order to detect the content of folic acid simply and accurately, the present invention provides a method for detecting folic acid using a molecular imprinting electrochemical sensor. The present invention adopts a solvothermal method to synthesize a molybdenum disulfide-carbon dot composite material, modifies a glassy carbon electrode with a molybdenum disulfide-carbon dot composite material solution, and then uses o-phenylenediamine as a functional monomer to prepare a molecular imprinting electrochemical sensor having a specific recognition response to the template molecule folic acid on the surface of the glassy carbon electrode modified with molybdenum disulfide-carbon dot by electrochemical polymerization. The present invention modifies the glassy carbon electrode with a molybdenum disulfide-carbon dot solution, thereby improving the formation and chelation of hydrogen bonds with the target molecule. Combined with molecular imprinting technology, a molecular imprinting electrochemical sensor having a specific recognition response to folic acid molecules is prepared, and it is applied to the detection of folic acid under neutral conditions, which has simple operation, low cost, good sensitivity and strong anti-interference.

[0008] In the electrochemical detection method based on the molybdenum disulfide-carbon dot molecular imprinting electrochemical sensor of the present invention, the factors affecting the electrochemical performance mainly include: the preparation of the molybdenum disulfide-carbon dot composite material, the test medium and the selective response of the prepared sensor to the target molecule, etc. By optimizing the above conditions, an electrochemical sensor that responds to folic acid can be constructed.

[0009] The present invention provides a method for preparing a molecular imprinting electrochemical sensor, the method comprising the following steps:

[0010] (1) Synthesis of a molybdenum disulfide-carbon dot composite material: Molybdenum disulfide and chitosan are mixed in a molar ratio of (1-4):1, and then a molybdenum disulfide-carbon dot composite material is prepared by a solvent method;

[0011] (2) Preparing a modified electrode: adding water to the molybdenum disulfide-carbon dot composite material prepared in step (1) to disperse the dispersion, wherein the concentration of the dispersion is 5-15 mg / ml, and then mixing the dispersion with a chitosan solution having a concentration of 0.5 wt.%-2 wt.% in a volume ratio of (1-5):1, drop-coating the mixture on a polished glassy carbon electrode and drying the mixture to obtain a modified electrode;

[0012] (3) Preparation of molecular imprinting electrochemical sensor: folic acid, o-phenylenediamine and phosphate buffer are prepared into a molecular imprinting electropolymerization solution, the modified electrode prepared in step (2) is placed in the polymerization solution to polymerize into a film, and the folic acid is eluted with an alkaline solution to obtain a molecular imprinting electrochemical sensor.

[0013] In one embodiment of the present invention, before synthesizing the molybdenum disulfide-carbon dot composite material, the blocky molybdenum disulfide needs to be exfoliated. The specific method is: take the ionic liquid, molybdenum disulfide, and chitosan and mix them, then grind them for 0.5 to 3 hours, wash and centrifuge to obtain the exfoliated molybdenum disulfide nanosheets and chitosan.

[0014] In one embodiment of the present invention, the ionic liquid includes 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-butylimidazolium acetate, and 1-butyl-3-butylimidazolium bromide.

[0015] In one embodiment of the present invention, the ionic liquid, molybdenum disulfide and chitosan are mixed and ground, and then acetone is added for washing, and then centrifuged at a speed of 8000-12000 rpm for 6 min-15 min, and then washed 2-5 times with an acetic acid solution with a volume fraction of 0.1%-5%; the sediment produced by centrifugation is dispersed with deionized water, and then centrifuged at a speed of 800-1200 rpm for 6 min-15 min, and after centrifugation, the upper layer of liquid is transferred and the deposited blocky molybdenum disulfide is discarded; then, centrifuged at a speed of 10000 rpm for 6-15 min, the dark green liquid in the upper layer is removed, and the lower layer of sediment is the exfoliated molybdenum disulfide nanosheets and chitosan.

[0016] In one embodiment of the present invention, the reaction conditions of the solvent method are: reacting at a temperature of 180° C. to 200° C. for 10 h to 14 h.

[0017] In one embodiment of the present invention, the molybdenum disulfide nanosheets and chitosan are dispersed with ethylene glycol and stirred for 20-40 minutes. After the stirring, they are poured into a reactor and reacted at a temperature of 180°C to 200°C for 10h to 14h. After the reaction is completed, they are cooled, the lower layer of solid sediment is removed and transferred to a centrifuge tube, and they are centrifuged and washed three times with deionized water and anhydrous ethanol respectively, and finally placed in a vacuum drying oven at 40°C to 80°C for 8h to 24h to obtain a molybdenum disulfide-carbon dot composite material after drying.

[0018] In one embodiment of the present invention, the drying conditions in step (2) are: drying in an oven at 40° C.-70° C. for 10 min-30 min.

[0019] In one embodiment of the present invention, in the molecular imprinting electropolymerization solution, the molar ratio of folic acid, o-phenylenediamine and phosphate buffer is (1-16):4:50, and the pH value of the phosphate buffer is 7.

[0020] In one embodiment of the present invention, the cyclic voltammetry electropolymerization film forming method is specifically as follows: the prepared GCE / MoS2-CDs modified electrode is placed in a molecular imprinting electropolymerization solution, and electropolymerization is performed for 20 cycles by cyclic voltammetry in a potential range of -0.2V-0.6V, with a scan rate of 0.05VS -1 .

[0021] In one embodiment of the present invention, after the modified electrode is polymerized into a film, it is placed in a 0.05 mol / L-0.5 mol / L NaOH solution for elution.

[0022] The invention provides a molecular imprinting electrochemical sensor prepared by the method.

[0023] The present invention provides a method for detecting folic acid content, wherein the molecular imprinting electrochemical sensor is used.

[0024] In one embodiment of the present invention, the method for detecting folic acid content is: in a mixed solution of K3[Fe(CN)6] and KCl, a molecular imprinting electrochemical sensor is used as a working electrode, an Ag / AgCl electrode is used as a reference electrode, and a platinum wire electrode is used as an auxiliary electrode, and the electrochemical signal of folic acid is detected by differential pulse voltammetry.

[0025] [Beneficial Effects]:

[0026] The present invention provides a molecular imprinting electrochemical sensor based on a molybdenum disulfide-carbon dot composite modified electrode for highly sensitive recognition and specific response to folic acid in a neutral environment. In the present invention, the molybdenum disulfide-carbon dot composite material of the modified electrode is simple to prepare and inexpensive, and the concentration of folic acid can be quickly detected by differential pulse voltammetry. Specifically, within the concentration range of 60 μmol / L-5000 μmol / L, the folic acid concentration and the electrochemical signal are in a linear relationship, and as the folic acid concentration increases, the current value decreases, and the detection limit is 0.09 μmol / L, which has good sensitivity. At the same time, the molecular imprinting electrochemical sensor prepared by the present invention has a specific response to folic acid, and the current difference obtained for folic acid is the largest, while the current difference of other substances (such as dopamine hydrochloride, ascorbic acid, L-cysteine) is small, indicating that the molecular imprinting electrochemical sensor prepared by the present invention has strong anti-interference. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 1 is the cyclic voltammetry curve of different materials prepared in Example 1.

[0028] Figure 2 are the electrochemical performance curves of different materials; among them, A is a bare glassy carbon electrode, B is a MoS2-carbon dot modified electrode, C is an electrode modified after electropolymerization, and D is an electrode modified after elution.

[0029] Figure 3 The electrochemical response diagram of the prepared molecular imprinted electrode to different concentrations of folic acid.

[0030] Figure 4 This is the anti-interference performance diagram in Example 6. DETAILED DESCRIPTION

[0031] The glassy carbon electrode GCE used in the following examples is GC130, which was purchased from Tianjin Aida Hengsheng Technology Co., Ltd.

[0032] [Example 1]

[0033] (1) Synthesis of MoS2-Cdot Composite Materials

[0034] Take 500 μL of ionic liquid with a pipette, take molybdenum disulfide and chitosan, put them into an agate mortar together, and grind them thoroughly for 1 hour. Among them, the amount of molybdenum disulfide and chitosan is 0.1g and 0.05g respectively (molar ratio is 2:1). After grinding thoroughly, move them to a centrifuge tube and add acetone to wash. Put the centrifuge tube into a centrifuge, centrifuge it at a speed of 10000rmp for 10min, repeat the washing three times, and then wash it three times with an acetic acid solution with a volume fraction of 0.1%-5%. The sediment produced by centrifugation is dispersed with deionized water, and then centrifuged at a speed of 1000rmp for 10min. After centrifugation, transfer the upper layer of liquid to another centrifuge tube, and discard the deposited blocky molybdenum disulfide. Subsequently, centrifuge it at a speed of 10000rmp again, remove the dark green liquid on the upper layer, and the lower layer of sediment is the exfoliated molybdenum disulfide nanosheets and chitosan. Then, 40 ml of ethylene glycol was used to disperse the above-mentioned molybdenum disulfide nanosheets and chitosan, poured into a beaker, and magnetically stirred for 30 minutes. After stirring, poured into a stainless steel reactor and reacted at 200°C for 12 hours. After the reaction, the reaction liquid was naturally cooled, the upper clear liquid was poured out, and the lower solid sediment was transferred to a centrifuge tube, washed three times with deionized water and anhydrous ethanol respectively, and finally placed in a vacuum drying oven at 60°C for 24 hours to obtain a molybdenum disulfide-carbon dot composite material, recorded as MoS2-CDs-1.

[0035] Compared with the preparation method of MoS2-CDs-1, the molar ratio of MoS2 to chitosan was changed to 1:2 (the amounts of MoS2 and chitosan were 0.05 g and 0.1 g, respectively) and 4:1 (the amounts of MoS2 and chitosan were 0.2 g and 0.05 g, respectively), and the other preparation conditions were the same to obtain MoS2-CDs-2 and MoS2-CDs-3 composite materials.

[0036] Compared with the preparation method of molybdenum disulfide-carbon dots-1, the reaction time of the solvothermal reaction was changed to 10h and 14h respectively. Other preparation conditions were the same to obtain molybdenum disulfide-carbon dots composite materials, which were recorded as MoS2-CDs-4 and MoS2-CDs-5 respectively.

[0037] The electrochemical performance of the prepared MoS2-Cdot composite material and glassy carbon battery was tested by cyclic voltammetry. Figure 1 It can be seen that the current value of MoS2-Cdot-1 is the largest. At this time, the reaction conditions of the MoS2-Cdot composite material are a molar ratio of MoS2 to chitosan of 2:1 and a reaction at 200°C for 12 hours. That is, the test results show that the electrochemical performance of MoS2-Cdot-1 is optimal.

[0038] (2) Preparation of modified electrode: The composite material MoS2-CDs-1 prepared in step (1) was dispersed and diluted with deionized water to a concentration of 10 mg / ml, and then the diluted dispersion was mixed with a chitosan solution with a concentration of 1 wt%. The volume ratio of the dispersion and the chitosan solution was 3:1. 8 μL was taken with a microinjector and dropped on the polished glassy carbon electrode, and dried in an oven at 60°C for 15 min to obtain a modified electrode.

[0039] (3) Preparation of molecular imprinting electrochemical sensor: 100 mL of deionized water was used to prepare a molecular imprinting electropolymerization solution with a molar ratio of 1:1:50 for folic acid, o-phenylenediamine and phosphate buffer, wherein the amount of folic acid was 0.1 mmol. The modified electrode prepared in step (2) was placed in the molecular imprinting electropolymerization solution, and electropolymerized into a film in the molecular imprinting electropolymerization solution at pH 7.00 by cyclic voltammetry. The specific polymerization method was to conduct electropolymerization at 0.2 V with a 0.05 VS -1 The electropolymerization was carried out for 20 cycles using cyclic voltammetry at a scan rate of , and after the polymerization was completed, the template molecule was eluted with a 0.25 mol / L NaOH solution to obtain a molecularly imprinted electrochemical sensor.

[0040] [Example 2]

[0041] (1) Synthesis of molybdenum disulfide-carbon dot composite material: the same method as that for synthesizing MoS2-CDs-1 in Example 1;

[0042] (2) Preparation of modified electrode: the same as step (2) in Example 1;

[0043] (3) Preparation of molecular imprinting electrochemical sensor: 100 mL of deionized water was used to prepare a molecular imprinting electropolymerization solution with a molar ratio of 1:4:50 of folic acid, o-phenylenediamine and phosphate buffer, wherein the amount of folic acid was 0.1 mmol. The modified electrode prepared in step (2) was placed in the molecular imprinting electropolymerization solution, and electropolymerized into a film in the molecular imprinting electropolymerization solution at pH 7.00 by cyclic voltammetry. The polymerization method was the same as that in Example 1. After the polymerization was completed, the template molecule was eluted with a 0.25 mol / L NaOH solution to obtain a molecular imprinting electrochemical sensor.

[0044] [Example 3]

[0045] (1) Synthesis of molybdenum disulfide-carbon dot composite material: the same method as that for synthesizing MoS2-CDs-1 in Example 1;

[0046] (2) Preparation of modified electrode: the same as step (2) in Example 1;

[0047] (3) Preparation of molecular imprinting electrochemical sensor: 100 mL of deionized water was used to prepare a molecular imprinting electropolymerization solution with a molar ratio of 4:1:50 of folic acid, o-phenylenediamine and phosphate buffer, wherein the amount of folic acid was 0.4 mmol. The modified electrode prepared in step (2) was placed in the molecular imprinting electropolymerization solution, and electropolymerized into a film in the molecular imprinting electropolymerization solution at pH 7.00 by cyclic voltammetry. The polymerization method was the same as that in Example 1. After the polymerization was completed, the template molecule was eluted with a 0.25 mol / L NaOH solution to obtain a molecular imprinting electrochemical sensor.

[0048] [Example 4]

[0049] (1) Synthesis of molybdenum disulfide-carbon dot composite material: the same method as that for synthesizing MoS2-CDs-1 in Example 1;

[0050] (2) Preparation of modified electrode: the same as step (2) in Example 1;

[0051] (3) Preparation of molecular imprinting electrochemical sensor: 100 mL of deionized water was used to prepare a molecular imprinting electropolymerization solution with a molar ratio of 1:1:50 of folic acid, o-phenylenediamine and phosphate buffer, wherein the amount of folic acid was 0.1 mmol. The pH of the molecular imprinting electropolymerization solution was adjusted to 4.00, and the modified electrode prepared in step (2) was placed in the molecular imprinting electropolymerization solution. The modified electrode was electropolymerized into a film in the molecular imprinting electropolymerization solution of pH 4.00 by cyclic voltammetry. The polymerization method was the same as that in Example 1. After the polymerization was completed, the template molecule was eluted with a 0.25 mol / L NaOH solution to obtain a molecular imprinting electrochemical sensor.

[0052] [Example 5]

[0053] (1) Synthesis of molybdenum disulfide-carbon dot composite material: the same method as that for synthesizing MoS2-CDs-1 in Example 1;

[0054] (2) Preparation of modified electrode: the same as step (2) in Example 1;

[0055] (3) Preparation of molecular imprinting electrochemical sensor: 100 mL of deionized water was used to prepare a molecular imprinting electropolymerization solution with a molar ratio of 1:1:50 of folic acid, o-phenylenediamine and phosphate buffer, wherein the amount of folic acid was 0.1 mmol. The pH of the molecular imprinting electropolymerization solution was adjusted to 9.00, and the modified electrode prepared in step (2) was placed in the molecular imprinting electropolymerization solution. The modified electrode was electropolymerized into a film in the molecular imprinting electropolymerization solution of pH 9.00 by cyclic voltammetry. The polymerization method was the same as that in Example 1. After the polymerization was completed, the template molecule was eluted with a 0.25 mol / L NaOH solution to obtain a molecular imprinting electrochemical sensor.

[0056] [Example 6]

[0057] (1) Synthesis of molybdenum disulfide-carbon dot composite material: the same method as that for synthesizing MoS2-CDs-1 in Example 1;

[0058] (2) Preparation of modified electrode: the same as step (2) in Example 1;

[0059] (3) Preparation of molecular imprinting electrochemical sensor: 100 mL of deionized water was used to prepare a molecular imprinting electropolymerization solution with a molar ratio of 1:1:50 of folic acid, o-phenylenediamine and phosphate buffer, wherein the amount of folic acid was 0.1 mmol. The pH of the molecular imprinting electropolymerization solution was adjusted to 11.00, and the modified electrode prepared in step (2) was placed in the molecular imprinting electropolymerization solution. The modified electrode was electropolymerized into a film in the molecular imprinting electropolymerization solution of pH 11.00 by cyclic voltammetry. The polymerization method was the same as that in Example 1. After the polymerization was completed, the template molecule was eluted with a 0.25 mol / L NaOH solution to obtain a molecular imprinting electrochemical sensor.

[0060] Electrochemical performance test:

[0061] The electrochemical properties of the above materials were confirmed by the cyclic voltammetric behavior of the bare glassy carbon electrode (A), the molybdenum disulfide-carbon dot modified electrode (B) (the modified electrode prepared in step (2) of Example 1), the electropolymerized modified electrode (C) (the electropolymerized modified electrode prepared in step (3) of Example 1), and the eluted modified electrode (D) (the eluted modified electrode prepared in step (3) of Example 1) in potassium ferrocyanide (see Appendix). Figure 2 ).Depend on Figure 2 It can be seen that the current value of the MoS2-C dot modified electrode (B) is the largest and greater than the current value of the bare glassy carbon electrode (A), indicating that the MoS2-C dot composite material has been modified. In the subsequent electropolymerization process, the current value of the modified electrode (C) after electropolymerization is the smallest, indicating that the molecular imprinting membrane has been completely electropolymerized on the MoS2-C dot modified electrode (B). During the elution process, due to the elution of the template molecule folic acid, holes appeared in the molecular imprinting membrane, and the current value was detected, indicating that the molecular imprinting electrochemical sensor (D) has been obtained at this time.

[0062] Study on the detection performance of folic acid by molecular imprinting electrochemical sensor

[0063] In a mixed solution of 5mmol / L K3[Fe(CN)6] and 0.1mol / L KCl, the molecular imprinting electrochemical sensor prepared in Example 1 was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, and the platinum wire electrode was used as the auxiliary electrode. The electrochemical signal was detected by differential pulse voltammetry. Figure 3The electrochemical response diagram of the prepared molecular imprinted electrode to different concentrations of folic acid shows that within the concentration range of 60μmol / L-5000μmol / L, there is a linear relationship between folic acid concentration and current difference. As the folic acid concentration increases, the current value decreases, and the detection limit is 0.09μmol / L.

[0064] In Examples 1 to 3, after changing the dosage ratio of folic acid, o-phenylenediamine and phosphate buffer, the electrochemical signal was detected by differential pulse voltammetry, and it was found that when the dosage ratio of folic acid, o-phenylenediamine and phosphate buffer was 1:1:50, the current difference detected by the molecular imprinting electrochemical sensor for folic acid was large and could form a good linear relationship with the folic acid concentration. When the dosage ratio of folic acid, o-phenylenediamine and phosphate buffer was not appropriate, the current difference would be reduced compared to the optimal situation.

[0065] In Examples 4 to 6, after changing the pH value during the electropolymerization reaction, the electrochemical signal was detected by differential pulse voltammetry, and it was found that when the pH was 7, the current difference detected by the molecular imprinting electrochemical sensor for folic acid was large and could form a good linear relationship with the folic acid concentration. When the pH value was not appropriate, the current difference would be smaller than the optimal case.

[0066] Evaluation of Anti-interference of Analytical Methods

[0067] In a mixed solution of 5mmol / L K3[Fe(CN)6] and 0.1mol / L KCl, the molecular imprinting electrochemical sensor prepared in Example 1 was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, and the platinum wire electrode was used as the auxiliary electrode. The electrochemical signal was detected by differential pulse voltammetry, and the electrochemical response signals of ascorbic acid, dopamine, and L-cysteine ​​were detected. The anti-interference performance of the method was evaluated by the current change. Figure 4 The figure is an anti-interference performance diagram. The test substances in the figure are folic acid, dopamine hydrochloride, ascorbic acid, and L-cysteine. Through the detection of the electrochemical signals of folic acid, dopamine hydrochloride, ascorbic acid, and L-cysteine ​​by differential pulse voltammetry, it is found that the prepared molecular imprinting electrochemical sensor has a specific response to folic acid, and the obtained current difference is the largest, while the current difference of the other three substances is smaller.

[0068] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a molecularly imprinted electrochemical sensor, It is characterized in that The method comprises the following steps: (1) Synthesis of MoS2-Cdot composite materials: ionic liquid, MoS2, and chitosan were mixed and ground for 0.5-3 h, wherein MoS2 and chitosan were mixed in a molar ratio of (1-4):1, washed and centrifuged to obtain exfoliated MoS2 nanosheets and chitosan; then, MoS2-Cdot composite materials were prepared by a solvent method at a temperature of 180°C-200°C for 10 h-14 h; (2) Preparing a modified electrode: adding water to the molybdenum disulfide-carbon dot composite material prepared in step (1) to disperse the mixture to obtain a dispersion having a concentration of 5 to 15 mg / ml, and then mixing the dispersion with a chitosan solution having a concentration of 0.5 wt.% to 2 wt.% in a volume ratio of (1 to 5):1, drop-coating the mixture on a polished glassy carbon electrode and drying the mixture to obtain a modified electrode; (3) Preparation of molecular imprinting electrochemical sensor: prepare molecular imprinting electropolymerization solution with folic acid, o-phenylenediamine and phosphate buffer, place the modified electrode prepared in step (2) in the polymerization solution to polymerize into film, place the modified electrode in 0.05 mol / L~0.5 mol / L NaOH solution to elute folic acid to obtain a molecular imprinting electrochemical sensor; in the molecular imprinting electropolymerization solution, the molar ratio of folic acid, o-phenylenediamine and phosphate buffer is 1:1:50; adjust the pH of the molecular imprinting electropolymerization solution to 7; the specific method of polymerizing film is: place the modified electrode prepared in step (2) in the molecular imprinting electropolymerization solution, and perform electropolymerization for 20 cycles in the potential range of -0.2 V~0.6 V by cyclic voltammetry technique, with a scan rate of 0.05 V s -1 .

2. The method according to claim 1, It is characterized in that The ionic liquid includes 1-butyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-butylimidazolium acetate, and 1-butyl-3-butylimidazolium bromide.

3. A molecularly imprinted electrochemical sensor prepared according to the method according to any one of claims 1 to 2.

4. A method for detecting folic acid content, It is characterized in that The method utilizes the molecular imprinted electrochemical sensor described in claim 3.

5. The method according to claim 4, It is characterized in that The method is specifically as follows: 3 [Fe(CN) 6 ] and KCl in a mixed solution, the electrochemical signal of folic acid was detected by differential pulse voltammetry using molecular imprinting electrochemical sensor as working electrode, Ag / AgCl electrode as reference electrode and platinum wire electrode as auxiliary electrode.